Discrepancies in Adolescents’ and their Mothers’ Perceptions of the Family and Adolescent Externalizing Problems - Ohannessian, Christine McCauley (2012)
The goal of this study was to examine whether adolescent-mother discrepancies in perceptions of the family predict later adolescent externalizing problems and/or whether adolescent externalizing problems predict later adolescent-mother discrepancies in perceptions of the family. In the spring of 2007 (Time 1) and 2008 (Time 2), surveys were administered to 125 15-18 year-old adolescent and their mothers. SEM results indicated that greater discrepancies in adolescent-mother perceptions of the family predicted higher levels of adolescent externalizing symptomatology (as reported by both adolescents and their mothers). In contrast, higher levels of externalizing symptomatology did not predict later discrepancies in adolescent-mother perceptions of the family. These findings suggest that research on adolescent adjustment should not solely rely on perceptions of the adolescent. In addition, the results highlight the importance of taking both directions of effect into consideration when examining the family and adolescent adjustment.